Franklin D. Roosevelt : the New Deal and war - Heale, M. J. (Lancaster pamphlets., 1999)
This compact study assesses the personality, political and economic policies in war and peace, of America's longest-serving president and one of the most important political figures of the twentieth century, Franklin. D. Roosevelt. Also providing an overview of the America over which Roosevelt presided, the book offers a concise survey of both domestic and foreign affairs.